PERANCANGAN DAN IMPLEMENTASI PAPAN JADWAL PERKULIAHAN BERDASARKAN SISTEM PENJADWALAN OTOMATIS - Johan K. W., Johan K. W.; Adrianto H., Adrianto H.; Marsolim, Marsolim (TESLA Jurnal Teknik Elektro UNTAR, 2006)
An automated lecture-schedule-board for students is provided. The board designed allows lecturers to enter changes on their teaching schedule and display the changes live automatically. The system is implemented using a microcontroller chip and an LED Matrix board on a Printed Circuit Board (PCB).